1995
DOI: 10.1111/j.1469-8137.1995.tb03005.x
|View full text |Cite
|
Sign up to set email alerts
|

Gametes with the somatic chromosome number: mechanisms of their formation and role in the evolution of autopolyploid plants

Abstract: summary The production of 2n gametes in plants, i.e. gametes with a somatic chromosome number, is considered to be the dominant process involved in the origin of polyploid plants. In this review, we provide a synthesis of current knowledge concerning the production of 2n gametes. Firstly, we describe the different methods used to detect and quantify the production of 2n gametes in plants, which include morphological and flow cytometry screening of the occurrence of 2n pollen, the analysis of crosses among dipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
609
2
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 552 publications
(642 citation statements)
references
References 187 publications
(458 reference statements)
17
609
2
3
Order By: Relevance
“…Principally, the observed pattern can be ascribed to the formation of anucleate, haploid and unreduced 2n pollen. In modern plants, pollen size is related to the number of chromosomes with increasing pollen volume at higher ploidy levels [9,[19][20][21][22][32][33][34][35]. While the number of pollen openings has been reported to vary in some polyploidy angiosperms [36], in this study, the number of pores and the furrows of Classopollis remains constant.…”
Section: (B) Classopollis Pollen Size Analysismentioning
confidence: 81%
See 1 more Smart Citation
“…Principally, the observed pattern can be ascribed to the formation of anucleate, haploid and unreduced 2n pollen. In modern plants, pollen size is related to the number of chromosomes with increasing pollen volume at higher ploidy levels [9,[19][20][21][22][32][33][34][35]. While the number of pollen openings has been reported to vary in some polyploidy angiosperms [36], in this study, the number of pores and the furrows of Classopollis remains constant.…”
Section: (B) Classopollis Pollen Size Analysismentioning
confidence: 81%
“…Unreduced gametes have been observed in many modern polyploid mutants and can be generated by a variety of cytological mechanisms [9,10,32]. In plants where unreduced gametes were found, unreduced pollen is formed by anomalies occurring during meiotic cell division.…”
Section: Discussionmentioning
confidence: 99%
“…The most important mechanism leading to polyploid plants is formation of the gametes with a diploid chromosome number (Bretagnolle and Thompson 1995). Diploid gametes can be produced in several ways, and cytomixis might well be one of them (Falistocco et al 1995;Ghaffari 2006;Lattoo et al 2006).…”
Section: Causes and Consequencesmentioning
confidence: 99%
“…It has been shown that 2n gametes in Brachiaria brizantha are produced from total absence either of the first or the second cytokinesis [33]. Further, influence of seasonal and environmental factors such as high and low temperature on 2n gamete formation have been shown [31]. Besides, cytomixis might have produced un-reduced pollen grains in this species.…”
Section: Introduction the Mountain Sorrel (Oxyria Digynamentioning
confidence: 99%
“…Un-reduced (2n) pollen grains. The trend to form 2n gametes in plants is highly variable and it varies among individuals within a single taxonomic group or even among flowers of an individual plant [31]. The production of unreduced gametes is heritable, governed by many genes and increases with increasing environmental stress, eg.…”
Section: Introduction the Mountain Sorrel (Oxyria Digynamentioning
confidence: 99%